A review of the effects and molecular mechanisms of dimethylcurcumin (ASC‐J9) on androgen receptor‐related diseases. (11th January 2021) - Hu, Hang; Zhou, Huan; Xu, Defeng
Abstract: Dimethylcurcumin (ASC‐J9) is a curcumin analogue capable of inhibiting prostate cancer cell proliferation. The mechanism is associated with the unique role of ASC‐J9 in enhancing androgen receptor (AR) degradation. So far, ASC‐J9 has been investigated in typical AR‐associated diseases such as prostate cancer, benign prostatic hypertrophy, bladder cancer, renal diseases, liver diseases, cardiovascular diseases, cutaneous wound, spinal and bulbar muscular atrophy, ovarian cancer and melanoma, exhibiting great potentials in disease control. In this review, the effects and molecular mechanisms of ASC‐J9 on various AR‐associated diseases are summarized. Importantly, the effects of ASC‐J9 and AR antagonists enzalutamide/bicalutamide on prostate cancer are compared in detail and crucial differences are highlighted. At last, the pharmacological effects of ASC‐J9 are summarized and the future applications of ASC‐J9 in AR‐associated disease control are discussed. Abstract : Dimethylcurcumin (ASC‐J9) is a curcumin analogue capable of inhibiting prostate cancer cell proliferation through a unique mechanism of enhancing androgen receptor (AR) degradation. The effects and molecular mechanisms of ASC‐J9 on various AR‐associated diseases such as prostate cancer, benign prostatic hypertrophy, bladder cancer, renal diseases, liver diseases and cardiovascular diseases are summarized systematically, and the future application of ASC‐J9 in AR‐associated disease control is discussed.